Strategi Pemerintah Kota Bekasi dalam Pengembangan Wisata Situ Rawagede Bojong Menteng Rawalumbu Bekasi - Alexander, Chaidar Firdaus; Samudra, Azhari Aziz; Yulianti, Isnaeni (FIA Unkris Press, 2023)
This study aims to determine the Bekasi City Government's strategy so that Situ Rawa Gede Bojong Menteng tourism will be crowded and become a center of promotion and culture, then to find out what obstacles are faced in making Situ Rawa Gede Bojong Menteng tourism so many people know it. In this study using qualitative descriptive research. The research informants consisted of 1 person from the Promotion Section, 1 Tourism Implementation Staff, and 3 visitors who visited Situ Rawa Gede Bojong Menteng tourism. The results showed that (1) Maintaining the personality of the community for the people of the Situ Rawa Gede Bojong Menteng tourism area has been proven by changing the Situ into a function, (2) Sustainability of the function in the Situ Rawa Gede Bojong Menteng tourism by conducting directions to residents, (3) The quality of the environment in Situ Rawa Gede Tourism is by way of guarding, monitoring, maintaining, and managing for 24 hours in turn, (4) Promoting the economy can be called a budget, for the budget in developing Situ Rawa Gede Bojong Menteng tourism is not yet available, (5) Guidance for the community to promote tourism, (6) Strengthening Situ Rawa's promotion and culture Gede Bojong Menteng so far has not been optimal, because not all people of Bekasi City know the Situ Rawa Gede Bojong Menteng tourism object, (7) The plan to develop Situ Rawa Gede tourism on the management side, namely Bojong Menteng has submitted a proposal to request a budget, but haven't gotten clarity to date. (8) Control to Provide the right strategy by inviting the public to promote Situ Rawa Gede Bojong Menteng tourism, by cooperating with investors, (9) Facilities in Situ Rawa Gede tourism such as parking are still hitching a ride in the Arts Building, worship facilities still use saung, security facilities need to be added, service facilities are quite good